A New Overstrike from Abakainon - Molinari, Nicholas J. (KOINON: The International Journal of Classical Numismatic Studies, 2023)
This brief essay presents evidence for a new overstrike from Abakainon on an undertype from Messana. The coin is a bronze hemilitron weighing 9.60g and measuring 21.5mm. It dates to the period of the so-called ‘federal’ coinage of the Symmachcia, when the Greek and Italic peoples aligned with Timoleon against the Carthaginians, c. 343 to 339 BC. The obverse features the head of the nymph Sikelia to right within a dotted border. There are no known variations of the obverse type. The reverse of these coins features the forepart of Acheloios (of the Helikon) to right, with one of three arrangements of the ABAKAININΩN inscription. The weights of these coins vary considerably—from c. 7.90 to c. 13.57g, but all are considered the same denomination, the hemilitron.